Characterization of impregnated commercial rice husks activated carbon with monoethanolamine (mea) and diethanolamine (dea) as potential co2 adsorbent - Siti Noraishah, Masoum Raman (2014)
The studies characterization of impregnated activated carbon with monoethanolamine (MEA) and diethanolamine (DEA) as potential carbon dioxide (CO2) adsorbent was successfully performed. The adsorption capacity of the activated carbon can be increased by introducing the amine group on the surface of the adsorbent. MEA and DEA were selected as amino compounds for the binding process on the activated carbon surface. The synthesis of the impregnated activated carbon was prepared according to the concentration and mixture ratio. The physicochemical properties of the impregnated activated carbon were characterized by X-Ray Diffraction (XRD), Brunauer, Emmett and Teller (BET), Fourier Transform Infrared Spectroscopy (FTIR) and Field Emission Scanning Electron Microscopy (FESEM). The XRD analysis was used to determine the type of compound presence on the activated carbon surface. The result reveals that the diffraction angles around 21.66º to 22.18º were linked for pyrazole, ethanolamine and diethanolamine which prove the presence of hydrocarbon and amine on the activated carbon surfaces. From the BET analysis, the total surface area and pore volume decreased with the increase of concentration of MEA and DEA. The presence of amide functional groups in FTIR analysis at 3288 cm-1 and 1651 cm-1 band for the impregnated activated carbon proved that there was a reaction occurs between carboxyl groups on the activated carbon surfaces with amine bonded. As for FESEM analysis, it was shown that the morphology of the non-impregnated activated carbon contains many pores on its surface while the pores on the impregnated activated carbon with MEA and DEA were filled with amines according to the selected concentration. The findings signify the high potential of CO2 adsorption capacity as the characterization results shows a positive feedback towards the quantity of MEA and DEA in the impregnated activated carbon samples